Synergistic DNA and RNA binding of the Hox transcription factor Ultrabithorax coordinates splicing and shapes in vivo homeotic functions - Blanco, Constanza; Xiang, Wan; Boumpas, Panagiotis; Buvry, Elzéar; Scorcelletti, Maily; Hermon, Ashley Suraj; Wong, Jiemin; Merabet, Samir; Carnesecchi, Julie (Nucleic acids research, 2025)
The dual interaction of many transcription factors (TFs) with both DNA and RNA is an underexplored issue that could fundamentally reshape our understanding of gene regulation. We address this central issue by investigating the RNA binding activity of the Drosophila Hox TF Ultrabithorax (Ubx) in alternative splicing and morphogenesis. Relying on molecular and genetic interactions, we uncover a homodimerisation-dependent mechanism by which Ubx regulates splicing. Notably, this mechanism enables the decoupling of Ubx-DNA and -RNA binding activity in splicing. We identify a critical residue for Ubx-RNA binding and demonstrate the essential role of Ubx-RNA binding ability for its homeotic functions. Overall, we uncover a unique mechanism for Ubx-mediated splicing and underscore the critical contribution of synergistic DNA/RNA binding for its morphogenetic functions. These findings advance our understanding of co-transcriptional regulation and highlight the significance of TF-DNA/RNA synergistic function in shaping gene regulatory networks in living organisms.